2023
DOI: 10.1002/jmv.29007
|View full text |Cite
|
Sign up to set email alerts
|

Azvudine therapy of common COVID‐19 in hemodialysis patients

Abstract: There is no antiviral study on hemodialysis patients infected with coronavirus disease 2019 (COVID‐19), especially on the application of 2′‐deoxy‐2′‐β ‐fluoro‐4′‐azidocytidine (Azvudine, FNC) antiviral therapy. We conducted a multicenter observational study involving 1008 hemodialysis patients. After matching for age, sex, and other factors, 182 patients in the basic treatment group and 182 in the FNC group were included. The negative nucleic acid conversion rate of the FNC group was significantly higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Similarly, Toussi et al. ( 26 ) demonstrated that the safety of nirmatrelvir/ritonavir in patients with renal impairment was similar to that of azvudine ( 27 ). Adverse reactions during COVID-19 treatment require further exploration in future studies.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Toussi et al. ( 26 ) demonstrated that the safety of nirmatrelvir/ritonavir in patients with renal impairment was similar to that of azvudine ( 27 ). Adverse reactions during COVID-19 treatment require further exploration in future studies.…”
Section: Discussionmentioning
confidence: 93%
“…Seven studies [ 8 , 13 , 26 – 28 , 31 , 33 ] involving 2742 patients reported the incidence of adverse events in patients taking azvudine and SOC/PBO. The pooled estimate of the included studies revealed no significant difference between the two groups in terms of adverse events (RR = 1.03, 95% CI: 0.64 to 1.67, P = 0.87, I 2 = 87%, GRADE certainty: low) ( Fig 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings showed elevated risk for ALI in people receiving nirmatrelvir-ritonavir, but azvudine showed no additional adverse event rates compared to the control, the findings of which are consistent with previous reports. 30,31 This presents one more option for vulnerable populations, improving their prognosis, especially in low and middle-income countries.…”
Section: Safety Outcomesmentioning
confidence: 99%